Topology of OxlT, the Oxalate Transporter of Oxalobacter formigenes, Determined by Site-Directed Fluorescence Labeling - Ye, Liwen (American Society for Microbiology, 2001)
The topology of OxlT, the oxalate:formate exchange protein of Oxalobacter formigenes, was established by site-directed fluorescence labeling, a simple strategy that generates topological information in the context of the intact protein. Accessibility of cysteine to the fluorescent thiol-directed probe Oregon green maleimide (OGM) was examined for a panel of 34 single-cysteine variants, each generated in a His(9)-tagged cysteine-less host. The reaction with OGM was readily scored by examining the fluorescence profile after sodium dodecyl sulfate-polyacrylamide gel electrophoresis of material purified by Ni(2+)-linked affinity chromatography. A position was assigned an external location if its single-cysteine derivative reacted with OGM added to intact cells; a position was designated internal if OGM labeling required cell lysis. We also showed that labeling of external, but not internal, positions was blocked by prior exposure of cells to the impermeable and nonfluorescent thiol-specific agent ethyltrimethylammonium methanethiosulfonate. Of the 34 positions examined in this way, 29 were assigned unambiguously to either an internal or external location; 5 positions could not be assigned, since the target cysteine failed to react with OGM. There was no evidence of false-positive assignment. Our findings document a simple and rapid method for establishing the topology of a membrane protein and show that OxlT has 12 transmembrane segments, confirming inferences from hydropathy analysis.